Exploring benefits of applying Google Workspace for Education in English as a foreign language classroom - Pham Duc Thuan; Nguyen Thi Hong Hanh (International Journal of Evaluation and Research in Education (IJERE), 2024)
The application of technology in language classrooms is widely believed to benefit learners. In the context of teaching and learning English as a foreign language (EFL) for high school students in Vietnam, there are few studies on the benefits of applying Google Workspace for Education (GWE). This small-scale qualitative study seeks to explore the benefits of applying GWE as a technological solution in the EFL classroom with high school students. The participants were eight eleventh graders in the north of Vietnam learning English in evening classes at an English center. To collect data, the students were interviewed. The qualitative data was analyzed based on themes. The results indicated that the benefits of applying GWE were evident in enhanced attitude and motivation for learning and improved learning skills. Based on the results of this study, it is recommended that Google tools be utilized for English language learning and instruction.